“Like sheep among hungry wolves”. Jesuit missionary literature in the Amazonian borderlands of the Peruvian viceroyalty (late seventeenth and early eighteenth centuries) - Betrán Moya, José Luis (Cuadernos de Historia Moderna, 2014)
The second half of the seventeenth century was a period of advance and consolidation for the Jesuit missions in the northern and eastern borderlands of the Peruvian viceroyalty. The experiences of many missionaries are preserved in a vast missionary literature written by the members of the Society of Jesus itself. This literature went through a genuine ‘golden age’ at the time. On grounds of some of its most emblematic works, this article proposes an analysis of some characteristics defining the narrative structures of this literary genre, which played an important role in the Jesuit propaganda on evangelization in South America.
Keywords: Society of Jesus; missionary literature; Peruvian viceroyalty; sixteenth and seventeenth centuries